Kontribusi Pemikiran Kiai Terhadap Pengelolaan SMP Alfa Ali Masykur Sigentir Mojotengah Wonosobo - Muhamad Nur Yasin; Ngarifin Sihddiq; Vava Imam Agus Faisal (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
The background of this research is that there is a world of renewal in the world of education such as education that combines formal education with non-formal education which is reflected in Islamic boarding schools such as SMP Alfa Ali Masyur Mojotengah Wonosobo. This Islamic boarding school based school involves the kiai as the leader of the Islamic boarding school who takes part in managing the school. The purpose of this research is to find out how the kiai's thinking contributes to the management of SMP Alfa Ali Masyur Mojotengah Wonosobo. This research uses a descriptive qualitative research type. The results of this study are the concept of KH. Ahmad Rofik Masykur in developing education at SMP Alfa Ali Masykur Mojotengah Wonosobo was able to instill an attitude of discipline and get used to good morals. In school management, they are able to manage employees and create a special team in program development. The supporting factors for the development of the Alfa Ali Masykur Middle School institution are the enthusiasm of the management, the existence of good opinion among the outside community. Then the inhibiting factor for the contribution of the kiai's thinking in the management of Alfa Ali Masykur Middle School is the existence of changing government policies, administrators and students who suddenly leave.